2020
DOI: 10.3892/etm.2020.9246
|View full text |Cite
|
Sign up to set email alerts
|

Primary carnitine deficiency in two sisters with intractable epilepsy and reversible metabolic cardiomyopathy: Two case reports

Abstract: Primary carnitine deficiency (PCD) is a disorder of the carnitine cycle that results in defective fatty acid oxidation. When carnitine cannot be transported into the cells, fatty acid oxidation is impaired, resulting a variety of symptoms, such as chronic muscle weakness, cardiomyopathy, hypoglycemia and liver dysfunction. The clinical manifestations and outcomes of different cases with PCD vary among patients. The present case report focused on two sisters with PCD. The younger sister presented with intractab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Studies have shown that Carnitine deficiency was found in approximately 17% of patients with epilepsy (13). Yang et al (10) also reported a case of PCD with epilepsy. In the proband's older brother, the initial symptom was abdominal pain with an ongoing poor appetite and decreased endurance.…”
Section: Discussionmentioning
confidence: 96%
“…Studies have shown that Carnitine deficiency was found in approximately 17% of patients with epilepsy (13). Yang et al (10) also reported a case of PCD with epilepsy. In the proband's older brother, the initial symptom was abdominal pain with an ongoing poor appetite and decreased endurance.…”
Section: Discussionmentioning
confidence: 96%
“…which improved after carnitine supplementation [14]. Another study done by Xiyu-Fang Yang, showed the inability of the heart to maintain adequate circulation was improved after carnitine supplementation [15]. Perin F et al, in their study showed that a dilated cardiomyopathy cause due to carnitine deficiency was improved after oral supplementation with Lcarnitine [16].…”
Section: Discussionmentioning
confidence: 97%
“…The SLC22A5 gene (also known as OCTN2 ) codes for the organic cation transporter novel 2 and is associated with the development of primary carnitine deficiency and cardiomyopathy ( 62 , 63 ). Here we present a family with the index patient diagnosed with LVNC and three family members diagnosed with DCM (see Supplementary Table S3 ).…”
Section: Discussionmentioning
confidence: 99%